AB1062 Patterns of musculoskeletal system involvement in patients with type i and type ii diabetes mellitus. (15th June 2017) - Adrosy, TI; Hanafy, MI; Hamoud, HS; Negm, AA
Abstract : Background: Diabetes mellitus (DM) is a chronic disease, no known cure except in very specific situations. Musculoskeletal Utrasonography (MSUS) has a great sensitivity that can help clinical examination for the detection of peripheral enthesitis associated with DM Objectives: To study the different patterns of musculoskeletal (MSK) system affection in both types of diabetes mellitus (DM). Methods: We performed a retrospective single-center study on sixty five patients during the period from May 2014 to February 2015, to evaluate MSK manifestations in diabetic patients at Sayyed Galal University Hospital, Cairo, Egypt. Patients were identified as diabetics based on Diagnosis and Classification of Diabetes Mellitus diagnostic criteria (1997) (1). Clinical data, laboratory investigations, X-ray, musculoskeletal ultrasonography (MSUS) (2) and Bone mineral density was measured using Dual energy X-ray absorptiometry (DEXA) scan (3) were all collected from all patients. Results: We included 65 diabetic patients; of these 21 patients (32.31%) had type I diabetes while 44 patients (67.69%) had type II diabetes. Age in type I was 24.5±10.5 years while in type II was 50.1±8.44 years (P=0.001). DM type II showed higher BMI (P=0.001), fatigue (P=0.005), shoulder periarthritis (frozen shoulder) (P=0.034), knee osteoarthritis (P=0.002), cheiroarthropathy (P=0.016), anserine bursitis (P=0.001) and plantar fasciitis (P=0.003) than type I. Osteoporosis was found in both types but type II showed more prevalence 13/44 patients (29.5%) while type I showed only 3/21 (14.2%). No statistically significant difference between both groups as regard t-score in the three sites. MSUS showed increased prevalence of quadriceps tendon enthesophytes in type I (P=0.033), while Infrapatellar (P=0.023) and retrocalcaneal bursitis (P=0.001) were more prevalent in type II DM. Conclusions: Early evaluation of any diabetic patient regarding BMD by DEXA scan and soft tissue by MSUS seems to be beneficial for early detection of any abnormality and therefore early management and prevention of complications. References: American Diabetes Association. Diagnosis and classification of diabetes mellitus. Diabetes Care. 2013; 36. Blake GM and Fogelman I. DEXA scanning and its interpretation in osteoporosis. Hosp Med 2003; 64:521–5. Balint PV, Kane D, Wilson H, McInnes IB and Sturrock RD: Ultrasonography of entheseal insertions in the lower limb in spondyloarthropathy. Ann Rheum Dis 2002; 61:905–910. Disclosure of Interest: None declared